Ki67 in Gleason Pattern 3 as a Marker of the Presence of Higher-Grade Prostate Cancer. Issue 2 (February 2021) - Caputo, Alessandro; D'Antonio, Antonio; Memoli, Domenico; Sabbatino, Francesco; Altieri, Vincenzo; Zeppa, Pio
Abstract : Purpose: Prostate biopsies may undergrade up to half of all prostate cancers (PCs), delaying definitive treatment by up to 3 years. One cause of undergrading is the partial sampling inherent in the technique. Because of this, a prostate biopsy that appears to be Gleason 3+3=6 may come either from a true 3+3=6 tumor or from a higher-grade tumor that has been sampled only partially. The main goal of the present study is to identify a way to distinguish these 2 kinds of "Gleason 3+3=6" biopsies. Mounting evidence hints at the possibility that Gleason pattern 3 associated with higher-grade PC (aG3) is biologically distinct from pure Gleason pattern 3 (pG3). Materials and Methods: In this study, we used immunohistochemistry and computer-aided image analysis to compare the expression of Ki67, cyclin D1, MYC, and p53 between foci of aG3 and pG3, to search for a marker that could distinguish them. Results: The expression of Ki67 differed significantly between pG3 and aG3. The average Ki67 labeling index was 1.63% for pG3 and 7.62% for aG3 ( P <0.01); the average number of Ki67 + cells per high-power field was 17 for pG3 and 60 for aG3 ( P <0.01). The other markers did not differ significantly between pG3 and aG3. Conclusions: When a biopsy only shows Gleason pattern 3 PC, Ki67 immunohistochemistry could be used to distinguish the nodules of true Gleason score 3+3=6 from those that only appear to be 3+3=6 because of a sampling error. This would dramatically improve the diagnostic performance of prostate biopsies and the management of early PC.